Revealing key topics shifts in thermal barrier coatings (TBC) as indicators of technological developments for aerospace engines - Khor, Khiam Aik (2021)
Thermal barrier coating (TBC) systems reduce the temperature of the metallic substrate of aerospace engines, resulting in improved component durability, better fuel economy and performance. Scientific research and innovation on TBC systems evolves rapidly and diversely over the years. Hence, an understanding of the research and innovation pathways on TBC systems is extremely important for the future development of aerospace engines. This study examines research publications and patents on TBC during 1980–2019. While USA led the TBC publication output from 1980 to 2010, China takes the lead after 2011 and India too is emerging noticeably on TBC research. The citation impact of publications reveal key topic shifts. Distinct peaks identified for (1) materials sciences during 1998–2003; (2) energy during 2001–2007, and (3) chemical engineering during 2009–2018. The visual mappings of author keywords of the publications reveal the progress of TBC technology. Results show shifts in deposition techniques for TBC coating preparation, and thermal management in the engines. The journal papers cited by patents have low correlation to the highly cited papers. This paper introduced an innovation relevance indicator to gauge the relevance of an institution’s scientific research to technological innovation. This novel indicator reveals the industry relevant work among the active institutions and companies with patents in TBC technologies. Universities with significant number TBC patents fall into two broad categories, (1) those who have high (> 70%) collaborations on patents filed, and (2) those that filed patents without existing external collaborations.